(untitled) (Research, Society and Development, 2024)
The diffusion of management policy and socio-environmental sustainability are presented as an alternative in the field of public administration, where the participation of technical-administrative employees in education and teachers in the creation of a common good is a privilege of a deliberative participatory process. The objective of this research is to understand the process of management and socio-environmental sustainability in the context of the Institute of Exact and Natural Sciences of the Federal University of Pará (ICEN/UFPA), to understand the perception of administrative technical servants in education and professors managing administration in the decision of educational environment, as well as the applicability of environmental education. The methodological procedure was based on Normative Instruction 10/2012, in which a questionnaire was prepared with 28 open and closed questions. The questionnaire was answered by employees and professors from the faculties and departments working at the Institute. Data analysis showed that the idea of disseminating and using environmental education as an interdisciplinary and multidisciplinary tool as an environmental practice, implements the theoretical approach to ICEN/UFPA’s human resources management and socio-environmental sustainability processes.